Is focal cortical dysplasia sporadic? Family evidence for genetic susceptibility. Issue 3 (6th February 2014) - Leventer, Richard J.; Jansen, Floor E.; Mandelstam, Simone A.; Ho, Alice; Mohamed, Ismail; Sarnat, Harvey B.; Kato, Mitsuhiro; Fukasawa, Tatsuya; Saitsu, Hirotomo; Matsumoto, Naomichi; Itoh, Masayuki; Kalnins, Renate M.; et al.
Summary Focal cortical dysplasia is a common cortical malformation and an important cause of epilepsy. There is evidence for shared molecular mechanisms underlying cortical dysplasia, ganglioglioma, hemimegalencephaly, and dysembryoplastic neuroepithelial tumor. However, there are no familial reports of typical cortical dysplasia or co‐occurrence of cortical dysplasia and related lesions within the same pedigree. We report the clinical, imaging, and histologic features of six pedigrees with familial cortical dysplasia and related lesions. Twelve patients from six pedigrees were ascertained from pediatric and adult epilepsy centers, eleven of whom underwent epilepsy surgery. Pedigree data, clinical information, neuroimaging findings, and histopathologic features are presented. The families comprise brothers with focal cortical dysplasia, a male and his sister with focal cortical dysplasia, a female with focal cortical dysplasia and her brother with hemimegalencephaly, a female with focal cortical dysplasia and her female first cousin with ganglioglioma, a female with focal cortical dysplasia and her male cousin with dysembryoplastic neuroepithelial tumor, and a female and her nephew with focal cortical dysplasia. This series shows that focal cortical dysplasia can be familial and provides clinical evidence suggesting that cortical dysplasia, hemimegalencephaly, ganglioglioma, and dysembryoplastic neuroepithelial tumors may share common genetic determinants. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here.